Operations and supply management : the core - Jacobs, F. Robert (McGraw - Hill, 2008)
Jacobs and Chase continue to lead the field of operations management with cutting edge up-to-date content, technology, and motivation. Now, in this second edition Jacobs and Chase focus on the core concepts of operations and supply management. This condensed text was constructed with sections on the four essential core areas - strategy, process management, supply chain management, and inventory and control (supply and demand planning). This set of four core areas was first suggested by a panel of OM instructor's at the Decision Science Institute meeting, and has been verified by market research which examined course syllabi from across the US. The second edition provides increased emphasis on supply management concepts, integrates sustainability as a strategic consideration, and includes updated company applications, problems, and cases.